Assessment of Desired Core Competencies and its Acquisition Barriers of Agricultural Extension Advisors in Nepal - Mehta, R. K.; Singh, O. P.; Sigdel, U. P.; Joshi, N. R. (Journal of Agriculture and Environment, 2021)
Modern agriculture is the era of 21st century. Competency is an indispensable in every aspect of delivering services to their ultimate users. Competency is integration of skills, knowledge, attitude and behavior that trigger to perform the delegated services in precise and methodical manner. The objective of this study was to identify important core competency required and its acquisition barrier for extension advisors of Nepalese agriculture extension service. Data were obtained using survey questionnaire from officers working at federal, state and local government offices of the selected 18 districts. The questionnaire was composed of open and close-ended questions based on 56 indicators of the nine core competencies. The descriptive statistics were used to analyze the responses. The findings indicated respondent perceptions on its all nine core competencies- program planning, program implementation, communication skills, extension education and information technology, program evaluation, personal and professional development, diversity, subject matter expertise and emotional intelligence from important to very important ranges. Subject matter expertise was perceived most important and communication skills as least one. Subject matter expertise, extension education and information technology skills positively correlate with education. The limited training opportunities and high cost for acquiring training personally are major barriers to gain competencies.